Math, asked by sharmaji, 1 year ago

(x+1)(2x+8)=(x+7)(x+3)

Answers

Answered by AcharyaVII
2
(x+1)(2x+8)=(x+7)(x+3)=2x²+8x+2x+8=x²+3x+7x+21
=2x²-x²+8x+2x-3x-7x=21-8
=x²=13
or, x=√13
or,x=+3.61 or - 3.61 (approx)
Ans:x=+3.61 or - 3.61 (approx)

AcharyaVII: Click on the yellow buttion above
AcharyaVII: *button
Answered by lohithanaidu
2
(x+1)(2x+8) = 2x²+10x +8
(x+7)(x+3)   = x²+10x+21
given that (x+1)(2x+8) = (x+7)(x+3)
              ⇒2x²+10x+8 = x²+10x+21
              ⇒x²=13
              ⇒x=√13 .

coolsid: (x+1)(2x+8)=(x+7)(x+3)=2x²+8x+2x+8=x²+3x+7x+21
=2x²-x²+8x+2x-3x-7x=21-8
=x²=13
x=√13
Similar questions